Operational stability prediction in milling based on impact tests. (15th March 2018) - Kiss, Adam K.; Hajdu, David; Bachrathy, Daniel; Stepan, Gabor
Highlights: Floquet multiplier is identified experimentally with operational impact test. In the proposed method, no system parameter identification is required as an input. Stability boundary can be extrapolated even if stable cutting operations are performed. Comb filtering technique is applied to subtract irrelevant periodic components. The theoretical part is extended by means of experimental validation. Abstract: Chatter detection is usually based on the analysis of measured signals captured during cutting processes. These techniques, however, often give ambiguous results close to the stability boundaries, which is a major limitation in industrial applications. In this paper, an experimental chatter detection method is proposed based on the system's response for perturbations during the machining process, and no system parameter identification is required. The proposed method identifies the dominant characteristic multiplier of the periodic dynamical system that models the milling process. The variation of the modulus of the largest characteristic multiplier can also be monitored, the stability boundary can precisely be extrapolated, while the manufacturing parameters are still kept in the chatter-free region. The method is derived in details, and also verified experimentally in laboratory environment.